The nature, causes and extent of land cover changes in Gamtoos River Estuary, Eastern Cape Province, South Africa: 1991-2017 - Ndude, Mhlanganisi Africa; Gwena, Kudzanai Rosebud; Hamandawana, Hamisai (MDPI, 2022)
Multi-date remotely sensed SPOT images of 1991, 2000, 2009 and 2017 were used to reconstruct changes in land cover in the Gamtoos River Estuary, Eastern Cape province, South Africa. These images were complemented by near-anniversary aerial photographs and Google Earth images that were used as ancillary sources of ground truth. The long-term trend direction of change was determined by calculating percentage changes and performing linear trend analysis. The magnitude of change was established by calculating Sen Slope estimates (SSE) and the influence of climate change on changes in land cover tested by correlating changes in rainfall and different cover types. The greatest and lowest changes were for noncultivated land and surface water (−7.94%, y = −1.2032x + 21.275, SSE = −0.292, and 0.44%, y = −0.4261x + 9.657, SSE = 0.007, respectively). Correlations between rainfall and all cover types were weak and ranged between 0.453816 and −0.643962. Rainfall exhibited a significant decrease (p = 0.0411, σ 0.05; y = −7.175x + 734.55, SSE = −11.130) that was highly correlated with changes in surface water distribution (0.813709, Critical R = 0.805). Overall, the results of this investigation point to the combined influence of climate change and human agency, with the latter tending to play a more prominent role by exerting increasing pressure on the environment’s natural supporting potentials. We therefore urge the scientific community to continue exploring actionable interventions that can be used to enhance the sustainability of this ecosystem and others elsewhere
Keywords: Land cover change; Climate change; Estuary